Fatal Outcome of Disseminated Strongyloidiasis despite Detectable Plasma and Cerebrospinal Levels of Orally Administered Ivermectin - Charles E. Rose; Christopher A. Paciullo; David R. Kelly; Mark J. Dougherty; Lawrence L. Fleckenstein (Journal of Parasitology Research)
Strongyloides stercoralis affects over 100 million people worldwide. Those people most susceptible to infection are those with an immunocompromising condition, such as cancer or human immunodeficiency virus (HIV). Local disease may spread throughout the body of the host, causing a condition termed disseminated strongyloidiasis. Standard treatment for Strongyloides stercoralis infection is oral ivermectin. We describe a patient with chronic lymphocytic leukemia diagnosed with disseminated strongyloidiasis two weeks after initial presentation. After repeated dosing of oral ivermectin with no clinical response, serum and cerebral spinal fluid (CSF) concentrations of ivermectin were measured to assess absorption. The peak serum concentration of 49.3 ng/mL correlated with a CSF concentration of 0.14 ng/mL. Despite these concentrations, the patient eventually succumbed to multi-system organ failure. We discuss the reasons for treatment failure and explore the utility of measuring ivermectin concentrations.